Write the function f(x) - 2x^2 - 24x + 76 in vertex form and identify its vertex

f(x)=- 2x^{2} - 24x + 76

y = - 2x^{2} - 24x + 76 = -2(x^{2}+12x+36)+148

y-148=-2(x+6)^{2}

vertex (-6,148)

f(x)=- 2x^{2} - 24x - 76

y = - 2x^{2} - 24x - 76 = -2(x^{2}+12x+36)-4

y+4 =-2(x+6)^{2}

vertex (-6,-4)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up